Esporotricose felina: distribuição das lesões e caracterização anatomopatológica em gatos utilizando diversos métodos de diagnóstico - Ágna Ferreira Santos (2019)
Sporotrichosis is a chronic deep fungal infection of the skin caused by the genus Sporothrix spp. The disease has cutaneous, lympho-cutaneous and extracutaneous forms, although the last one has not been studied and clarified yet. The aim of this study was to characterize by histopathology and immunohistochemistry exams, the cutaneous and extracutaneous lesions of sporotrichosis in cats from metropolitan region of Belo Horizonte. In the period from March 2018 to March 2019, 110 cats rescued by the Zoonoses Control Center of Belo Horizonte, were evaluated with clinical suspicion of feline sporotrichosis, confirmed or not by culture and isolation. Cats unable to be treated were euthanized. After euthanasia, the animals were evaluated by macroscopic, cytopathological, histopathological and immunohistochemical exams. Molecular tests to confirm the Sporothrix species were also performed. Out of 110 animals, 74 were positive for Sporothrix spp. on routine hematoxylin and eosin staining, 30 by immunohistochemistry and two only by fungal culture and PCR. Cytopathology and histopathology exams were efficient in the diagnosis of the disease, although in cats with lesions containing low fungal load, immunohistochemistry was needed to confirm the agent. The most common histopathological findings on the skin were pyogranulomatous dermatitis, histiocytic and plasmacytic dermatitis and granulomatous dermatitis, with different amount of yeasts in the lesions. The extracutaneous findings were histiocytic and plasmacytic or pyogranulomatous rhinitis/rhinosinusitis, sinusoidal histiocytic lymphadenitis, granulomatous lymphadenitis, histioplasmacytic and neutrophilic pneumonia, histiolymphoplasmacytic conjunctivitis, granulomatous glossitis, granulomatous and necrotic periorchitis and histiocytic meningitis, all with many different numbers of yeasts. In four of the 110 cats with ulcerative skin lesions, other diseases were diagnosed; three cases of squamous cell carcinoma and one case of cutaneous nocardiosis, being considered important for the differential diagnosis.